Pelatihan Sport Massage Berbantuan Dual Vibration Untuk Tindakan Preventif Delayed Onset Muscle Soreness (DOMS) Bagi Tenaga Pengajar SMAN Keberbakatan Olahraga Bengkulu - Raibowo, Septian; Ilahi, Bogy Restu; Rizky, Oddie Barnanda; Prabowo, Andika; Yarmani, Yarmani (Jurnal Pengabdian Olahraga Masyarakat, 2025)
One of the many contributing elements to Bengkulu Province's declining sporting accomplishments is the teaching staff at SMANKO's ignorance of managing and recovering from sports injuries. Increasing knowledge and proficiency in dual vibration-assisted sports massage for the goal of preventing delayed onset muscle soreness (DOMs) is the aim of this community service project. The training materials are delivered in a manner that combines direct practice and demonstration techniques. The population that was utilized of all 35 teaching staff members of SMAN Keberbakatan Sport Province in Bengkulu. As a result of this activity, participants' knowledge and proficiency in dual vibration-assisted sports massage increased. However, the majority of pretest results—23 teaching staff members, or 65.7%—were in the extremely poor group the majority of teaching staff—57.1% in the very high category, 17.1% in the high category, and 20% in the medium groups. The paired samples test, or t-test, produced a sig. (2-tailed) value of = 0.001 0.05. According to the findings, dual vibration-assisted sports massage training improves the teaching staff at SMAN Keberbakatan Sport's knowledge and abilities in terms of delayed onset muscle soreness (DOMs) prevention.